A new species of South Asian Cnemaspis (Squamata: Gekkonidae) from the Eastern Ghats, India - Agarwal, Ishan; Bauer, Aaron M; Khandekar, Akshay (Zootaxa, 2020)
We describe a new species from within the South Asian clade of the polyphyletic gekkonid genus Cnemaspis from the Velikonda Range, in the Eastern Ghats, Andhra Pradesh, India. The new species is the smallest known Indian gekkonid and can be diagnosed from all Indian congeners by its small body size (SVL <29 mm), the absence of spine-like scales on flank, heterogeneous dorsal pholidosis, presence of precloacal pores and no femoral pores in males, tail with enlarged, strongly keeled, conical tubercles forming whorls, median row of sub-caudals smooth and slightly enlarged, and a distinct colour pattern. This is the 12th species of Cnemaspis to be described from outside the Western Ghats and is the first endemic from the Velikonda region of the Eastern Ghats. The new species is only known from its type locality, a lowland riparian habitat (<200 m asl.) in dry evergreen forest at the base of a 1200 m asl. peak. This discovery extends the range of the genus in peninsular India by 130–150 kilometres to the northeast and suggests the genus is likely to be even more widely distributed than understood. The new species is clearly allied to C. mysoriensis, C. otai and C. yercaudensis with which it shares superficial colour pattern and similar body size, but is the first species from outside the Western Ghats in which males lack femoral pores.